Low‐Iridium‐Content IrNiTa Metallic Glass Films as Intrinsically Active Catalysts for Hydrogen Evolution Reaction. Issue 4 (6th December 2019) - Wang, Zi‐Jian; Li, Ming‐Xing; Yu, Ji‐Hao; Ge, Xing‐Bo; Liu, Yan‐Hui; Wang, Wei‐Hua
Abstract: Although various catalytic materials have emerged for hydrogen evolution reaction (HER), it remains crucial to develop intrinsically effective catalysts with minimum uses of expensive and scarce precious metals. Metallic glasses (MGs) or amorphous alloys show up as attractive HER catalysts, but have so far limited to material forms and compositions that result in high precious‐metal loadings. Here, an Ir25 Ni33 Ta42 MG nanofilm exhibiting high intrinsic activity and superior stability at an ultralow Ir loading of 8.14 µg cm −2 for HER in 0.5 m H2 SO4 is reported. With an overpotential of 99 mV for a current density of 10 mA cm −2, a small Tafel slope of 35 mV dec −1, and high turnover frequencies of 1.76 and 19.3 H2 s −1 at 50 and 100 mV overpotentials, the glassy film is among the most intrinsically active HER catalysts, outcompetes any reported MG, representative sulfides, and phosphides, and compares favorably with other precious‐metal‐containing catalysts. The outstanding HER performance of the Ir25 Ni33 Ta42 MG film is attributed to the synergistic effect of the novel alloy system and amorphous structure, which may inspire the development of multicomponent alloys for heterogeneous catalysis. Abstract : An extremely flat low‐iridium‐content Ir25 Ni33 Ta42 metallic glass film with an ultralow Ir loading is presented as an intrinsically active and highly stable catalyst for the hydrogen evolution reaction (HER) in acids. This work provides a novel alloy system for HER in acids, and is helpful for the development of heterogeneous catalysts in multicomponent alloys.